Braking System Modeling and Brake Temperature Response to Repeated Cycle - Zaini Dalimus (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2014)
Braking safety is crucial while driving the passenger or commercial vehicles. Large amount of kinetic energy is absorbed by four brakes fitted in the vehicle. If the braking system fails to work, road accident could happen and may result in death. This research aims to model braking system together with vehicle in Matlab/Simulink software and measure actual brake temperature. First, brake characteristic and vehicle dynamic model were generated to estimate friction force and dissipated heat. Next, Arduino based prototype brake temperature monitoring was developed and tested on the road. From the experiment, it was found that brake temperature tends to increase steadily in long repeated deceleration and acceleration cycle.